Activating the tools of social media for innovative collaboration in the enterprise - Majchrzak, Ann; Fife, Elizabeth; Min, Qingfei; Pereira, Francis (Cham : Springer, 2014)
As enterprises become increasingly distributed, employees are less likely to be personally familiar with the people with whom they are collaborating. Past research has repeatedly demonstrated that lack of familiarity decreases the likelihood that employees will collaborate with other employees. However, the use of social media-especially wikis which we focus on-has the potential to change past traditions. Wikis offer the possibility of employees not only adding their own content, as they would with any knowledge management system, but also integrating their content with other content in a process called ''shaping.'' When diverse content is integrated, the possibility of innovation increases, especially when the process is a collaborative one. Therefore, wikis as a social media tool offer the opportunity of supporting collaborative innovation among employees. Despite the opportunity, most wikis in today's enterprises are used for knowledge capture and knowledge transfer, and not for collaborative innovation. In this report, we examine the opportunity provided by wikis, based on the current literature. We then examine the reasons why this opportunity may not be currently filled, based on the results of field research of four case studies and interviews with representatives at 12 companies known for their innovativeness. The findings of our field research led us to the development of two new instruments for the 2020 enterprise: (1) a Capability Maturity Model for the use of Enterprise Social Media for Collaborative Innovation and (2) a Readiness Checklist of Social Media Use For Collaborative Innovation
También en formato EPUB
Keywords: ADMINISTRACION -- PROCESAMIENTO DE DATOS; TECNOLOGÍA DE LA INFORMACIÓN; GESTION INDUSTRIAL; ADMINISTRACION DE SISTEMAS DE INFORMACION; MEDIOS DE COMUNICACION SOCIALES